TANGGUNG JAWAB NOTARIS TERHADAP AKTA YANG DIUBAH SECARA SEPIHAK (CONTOH KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 146/PDT/2018/PT.BDG.) - Michelle Starla Ongko; Ariawan Gunadi (Jurnal Hukum Adigama, 2019)
Renvoi is the changes that was made before the deed was signed by the parties. There is quite a difference between a change in the deed, which are made before signed and the change after signed. Whereas if the change was made after signed, the change must be made in the presence of the parties, witnesses, and the public notary, reported in an official statement of the event and give no regarding the matter to the original copy of the deed with notification of the date and number of the correction. If a Notary does not do as provided in the renvoi procedure, it may result in the deed being considered inauthentic. And could result in one of the party to suffer a loss in the foreseeable future and it could serves as a legal basis to claim compensation, damages plus interests and to be put on the public notary’s responsibility. Based on the example of the present case in Supreme Court Decree No. 146 / PDT / 2018 / PT.BDG, in the making of a rent-to-hire deed,  there is a difference between the original copy of the deed which are not similar with the copies that are given  to the respective parties. The original copy of the deed is full of correction scribbles, replacements, inserts, additions, and overlays, which are definitely not typing mistakes. Thus, the public notary has violated Article 48 of the Public Notary Act No. 2 of 2014.